2018
DOI: 10.1253/circj.cj-17-0104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mitral Valve Surgery in Patients With Dilated Cardiomyopathy and Severe Functional Mitral Regurgitation

Abstract: Background: Surgical treatment of functional mitral regurgitation (FMR) improves ventricular remodeling in patients with dilated cardiomyopathy (DCM). However, it is unclear whether surgical treatment improves long-term outcomes. We investigated the effects of mitral valve (MV) surgery in patients with DCM and FMR. Methods and Results:Of 525 patients with DCM hospitalized due to heart failure between January 1996 and September 2014, 70 who had severe FMR despite receiving optimal medical therapy were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, it has been reported that there was no significant survival benefit conferred by MVr for patients with FMR and nonischemic DCM. 8 However, Chung et al 18 reported that the correction of MR could improve the prognosis in these patients. In addition, Stone et al 24 in a cardiovascular outcomes assessment of the MitraClip percutaneous therapy (COPAT) study reported that transcatheter mitral-valve repair using the MitraClip device resulted in a lower rate of heart failure-related hospitalization and lower allcause death within 2 years of follow-up than medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that there was no significant survival benefit conferred by MVr for patients with FMR and nonischemic DCM. 8 However, Chung et al 18 reported that the correction of MR could improve the prognosis in these patients. In addition, Stone et al 24 in a cardiovascular outcomes assessment of the MitraClip percutaneous therapy (COPAT) study reported that transcatheter mitral-valve repair using the MitraClip device resulted in a lower rate of heart failure-related hospitalization and lower allcause death within 2 years of follow-up than medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients with FMR and nonischemic DCM are associated with multiple comorbidities and poor long-term survival, with only 30% of the 5-year survival. 2,4,18,19 With the majority of studies focusing on the prognostic impact of ischemic MR or mixed FMR including ischemic cardiomyopathy and nonischemic DCM, 7,[20][21][22] there are scarce reports demonstrating the outcomes in patients with FMR and nonischemic DCM. Additionally, it remains controversial whether MVr improves survival.…”
Section: Discussionmentioning
confidence: 99%